Materials Science Research and Development in India: A Scientometric Analysis of International Collaborative Output - Mohan, S.; Gupta, B.M.; Dhawan, S.M. (DESIDOC Journal of Library & Information Technology, 2003)
Materials science research in India is analysed for a period of five years (1995-1999), based on a study of papers published by Indian scientists in collaboration with foreign researchers, as covered in Material Science Citation Index (MSCI). The results indicate that materials science in India is broad based and covers most of the important sub-areas, and is based on inherent strength. Most of the work involved bilateral rather than multilateral collaboration. The top collaborating countries were the US, Germany, France, UK and Japan. Collaborative linkages with developing countries accounted for only about 10% of the total papers. Ten top Indian institutions contributed nearly 50% of the collaborated papers. The major areas of collaboration were theoretical studies, metals & alloys, electronic materials and super conducting materials. http://dx.doi.org/10.14429/dbit.23.2.3594